Distribution and occurrence of antibiotic resistance genes and microbial diversity in western Hainan's inshore seawaters: A seasonal study - Chi Yang; Yongqiang Qin; Yingying Zhang; Ardavan Farhadi; Sai Wang; Xiaoping Diao; Jia Xie (Emerging Contaminants)
Antibiotic resistance genes (ARGs) have become one of the threats to human health worldwide. In this study, SmartChip real-time fluorescent quantitative PCR and qPCR was employed to quantify the ARGs and mobile genetic elements (MGEs) at 24 sampling sites of western Hainan. High-throughput sequencing of 16S rRNA was utilized to analyze the structure of microbial communities. The correlation among ARGs, environmental factors, MGEs, and microbial diversity was analyzed to elucidate the distribution, possible sources, and potential hosts of ARGs during the dry and rainy seasons. The results showed that 122 ARG species with a 93.85 % detection rate and 13 MGE species with a 100 % detection in the inshore waters of western Hainan during the dry and rainy seasons. The absolute abundance of ARGs and MGEs was higher during the dry seasons compared to the rainy seasons. Among these, aminoglycoside resistance genes exhibited the highest absolute abundance during the dry season, followed by MLSB resistance genes, while peptide resistance genes demonstrated the lowest abundance. During the rainy season, the absolute abundance of aminoglycoside resistance genes is the highest, followed by sulfonamides resistance genes, while peptide resistance genes remain the least abundant. ARGs were significantly correlated with MGEs, suggesting that MGEs may mediate the horizontal transfer and spread of ARGs. Environmental factor analyses showed that Temperature, dissolved oxygen, and total phosphorus play a key role in affecting the spatial distribution of ARGs. At the phylum level, Proteobacteria, Actinobacteria, and Bacteroidetes are the core microorganisms during the dry and rainy seasons.